NEOLIBERALISM “À BRASILEIRA”: (Management and Connections Journal, 2022)
This theoretical essay sought to reflect on contemporary neoliberalism. The history of Brazil intersected by oppressions, which were systematically engendered and converged in racist, capitalist and heterocispatriarcal structures. I begin with the reflection that even capitalism, following a logic, is differentiated by the historical process in the modes of production and primitive accumulation situated in space and time. The historiographical thread allowed a trip to the past, not so distant, until the contemporary. The neoliberal model and the eminent death policy for society not considered productive in the Brazilian neoliberal models were highlighted. Finally, reflective questions were exposed to provoke new thinking from and in organizational studies and proposals for new approaches for future studies. The study contributes to organizational studies by reconstructing a silenced historical process and problematizing hegemonic perspectives in administration, which are imported from other socio-historical contexts in an uncritical and ahistorical manner, which contributes to the maintenance of the colonization of power /know.
Keywords: Neoliberalism; Race; Gender; Coloniality; Intersectionality